2017
DOI: 10.1152/ajprenal.00679.2016
|View full text |Cite
|
Sign up to set email alerts
|

Renal inflammation and injury are associated with lymphangiogenesis in hypertension

Abstract: Lymphatic vessels are vital for the trafficking of immune cells from the interstitium to draining lymph nodes during inflammation. Hypertension is associated with renal infiltration of activated immune cells and inflammation; however, it is unknown how renal lymphatic vessels change in hypertension. We hypothesized that renal macrophage infiltration and inflammation would cause increased lymphatic vessel density in hypertensive rats. Spontaneously hypertensive rats (SHR) that exhibit hypertension and renal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…In addition, recent studies strongly suggest the corelation between renal inflammation and hypertension [37, 38]. In this study, the mRNA level of TNF α elevated by NaCl was decreased with 6- gingerol treatment, and the regulation of TNF α by 6-gingerol was PPAR δ -dependent.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, recent studies strongly suggest the corelation between renal inflammation and hypertension [37, 38]. In this study, the mRNA level of TNF α elevated by NaCl was decreased with 6- gingerol treatment, and the regulation of TNF α by 6-gingerol was PPAR δ -dependent.…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, in all CKD a prominent accumulation of lymphatic vessels was present in association with MPS cell infiltration in the tubulointerstitium of the cortex. These newly formed lymphatic vessels, that is, de novo lymphangiogenesis, help to manage the increase in interstitial fluid related to inflammation (Kneedler et al, ; A. S. Lee et al, ; Matsui et al, ; Sakamoto et al, ; Seeger, Bonani, & Segerer, ; Suzuki et al, ; Yazdani et al, ). Kidney‐specific augmentation of lymphatic vessels before hypertensive stimuli have been shown to prevent renal immune cell accumulation and prevent the development of hypertension (Lopez Gelston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the prerequisite for the development of these lymphatic vessels is kidney injury independently from the presence of hypertension (Kneedler et al, ). Because high salt damages the kidney (Boero, Pignataro, & Quarello, ; Lambers Heerspink, Navis, & Ritz, ; McMahon, Campbell, Bauer, & Mudge, ; McMahon et al, ; Sanders, ; Saran et al, ; Wright & Cavanaugh, ), as in our study, we postulate that the observed induction of renal lymphangiogenesis is a consequence of salt aggression on renal tissue and not a high blood pressure effect.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in spontaneously hypertensive rats that exhibit hypertension combined with renal injury (SHR-A3 strain), lymphatic vessel density and macrophage infiltration into the kidney were both significantly elevated compared to normotensive Wistar-Kyoto (WKY) background controls (544), suggesting lymphatic network remodeling in response associated with renal diseases. Similar observations were also reported when comparing aged Fischer rats (20–24 months old), along with elevated inflammation and Vegfc/Vegfr3 expression, compared to 4-month old controls (544). Increased lymphatic vessel density has also been observed in mice that have hypertension due to salt sensitivity or inhibition of nitric oxide synthase activity.…”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%